Using the “ASKED” Model to Contrive Motivations and Teach Individuals with ASD to Ask wh-Questions in Natural Settings - Ostryn, Cheryl (Journal of the American Academy of Special Education Professionals, 2016)
Individuals with ASD are less likely to engage in social mands, such as wh-question asking, even though this skill is demonstrated in those without ASD as young as 18 months. Therefore, teaching wh-questions to individuals with ASD is an important element in the development of any communication program. This is the third published study in a series of wh-question asking studies, and utilizes the ASKED model in order to teach two wh-questions to individuals with ASD in natural environments. The ASKED model describes a systematic procedure for setting up environments in order to motivate and teach question asking, including the use of prompts and data collection. This study employed naturally occurring communicative partners to implement the ASKED model in a variety of natural settings, and results showed positive effects across all seven participants.